Dietary Habits in Patients with Chronic Spontaneous Urticaria: Evaluation of Food as Trigger of Symptoms Exacerbation - Jorge Sánchez; Andres Sánchez; Ricardo Cardona (Dermatology Research and Practice)
Background. Many patients with chronic spontaneous urticaria (CSU) identify different foods as triggers of their symptoms and frequently make dietary restrictions without enough information. Objective. To explore the diet habits of CSU patients and estimate the clinical impact of the foods most frequently reported to be suspect. Methodology. Patients were interrogated about their clinical history of urticaria. Skin prick test and sIgE serum were done for most frequently reported foods by patients. Food challenge test was also performed. A group of healthy subjects was included to compare the dietary habits and the results of the diagnostic tests. Results. Patients with CSU (n 245) and healthy (n 127) subjects were included. 164 (66%) subjects from CSU group and 31 (24%) from the control group reported at least one adverse reaction with foods. Food IgE sensitization was similar in both groups (17.5% versus 16.5%, respectively). 410 food challenge tests in 164 CSU patients and 38 in 38 control subjects were performed. 1.2% in CSU group and 0.7% in control group had a positive oral challenge test. Conclusion. Despite the high frequency of self-report by patients, foods are uncommon triggers of CSU. Nevertheless, food challenge tests have to be offered early during medical evaluation to avoid unnecessary restrictions.